Taxonomic characterization of Aphelenchoides besseyi sensu lato and the study of diseases angular leaf spot in jambu (Acmella oleracea) and green stem and foliar retention syndrome in soybean (Glycine max) - Silva, Marcela de Freitas (2023)
Aphelenchoides besseyi is considered one of the most threatening nematodes to global agriculture. Despite this, there is little information about genetic diversity, host range and some aspects related to its interaction with its host plants. Recently it was proposed to reclassify A. besseyi into a species complex composed of: A. besseyi sensu stricto, A. oryzae e A. pseudobesseyi. Thus, the objectives of this work were: i) to identify the species of Aphelenchoides causing angular leaf spot in jambu (Acmella oleracea); ii) to biologically and molecularly characterize populations of A. besseyi sensu lato from different hosts, comparing them with other populations from the A. besseyi species complex already described; iii) evaluate aspects of the interaction of this plant parasitic nematode with soybean through histopathological analyses. Morphological, morphometric, and phylogenetic characterizations were carried out, and A. pseudobesseyi was identified as the causal agent of angular leaf spot in jambu. Moreover, the biological characterization of A. besseyi s.l. populations from rice, jambu and soybean, indicated that they reproduce through amphimixis and exhibit sexual compatibility. Phylogenetic and species delimitation analyses, based on nuclear ribosomal and mitochondrial DNA, supported the presence of A. besseyi sensu stricto, A. oryzae, and A. pseudobesseyi within the A. besseyi species complex, with the populations in this study clustering within the A. pseudobesseyi clade. Furthermore, these populations infected soybean, cotton, common beans, and jambu, but they did not infect strawberry and rice. In the interaction of this nematode with soybean, A. pseudobesseyi migrates on the external parts of the plant, targeting shoots, leaves, flowers, and pods, causing alterations as hypertrophy, hyperplasia and cell collapse. However, the nematode is incapable of infecting the seeds. The results of this research point out that A. pseudobesseyi is the etiological agent of angular spot in jambu. All populations of the A. besseyi species complex studied, originating from different hosts, are A. pseudobesseyi. The evidence presented corroborates the recognition of A. oryzae, A. besseyi and A. pseudobesseyi as valid species. The mtCOI gene is the most suitable molecular marker for the phylogenetic study of populations of this species complex. In soybean crops, A. pseudobesseyi parasitism occurs mainly in the regions of sprouts, in leaves and flower buds, with the nematode migrating externally to the plant tissue until reaching such locations. On the leaf blade, the nematode penetrates the tissues, feeding on mesophyll cells. In other organs, parasitism occurs externally to the tissues. However, A. pseudobesseyi is not capable of infecting soybean seeds, and its spread through these is unlikely. Keywords: Foliar nematode. Phylogeny. Etiology. Histopathology